Yersinia pestis targets neutrophils via complement receptor 3. (25th November 2014) - Merritt, Peter M.; Nero, Thomas; Bohman, Lesley; Felek, Suleyman; Krukonis, Eric S.; Marketon, Melanie M.
Summary Yersinia species display a tropism for lymphoid tissues during infection, and the bacteria select innate immune cells for delivery of cytotoxic effectors by the type III secretion system. Yet, the mechanism for target cell selection remains a mystery. Here we investigate the interaction of Yersinia pestis with murine splenocytes to identify factors that participate in the targeting process. We find that interactions with primary immune cells rely on multiple factors. First, the bacterial adhesin Ail is required for efficient targeting of neutrophils in vivo. However, Ail does not appear to directly mediate binding to a specific cell type. Instead, we find that host serum factors direct Y. pestis to specific innate immune cells, particularly neutrophils. Importantly, specificity towards neutrophils was increased in the absence of bacterial adhesins because of reduced targeting of other cell types, but this phenotype was only visible in the presence of mouse serum. Addition of antibodies against complement receptor 3 and CD14 blocked target cell selection, suggesting that a combination of host factors participate in steering bacteria towards neutrophils during plague infection.